Z podróży włoskiej. Fra Angelico . Wniebowzięcie – o nieznanym wierszu Marii Konopnickiej z cyklu „Madonna” - Zwolińska, Anna (Colloquia Litteraria, 2023)
The article admonishes a forgotten and poorly recognised poem by Maria Konopnicka entitled „Fra Angelico. Wniebowzięcie”, which was first published in „Biblioteka Warszawska” in 1898 with the poet’s annotation: „Z cyklu Madonna”. Konopnicka included the above-mentioned lyrical cycle in the poetic volume „Italia”. The author of the article insists on a reminder of the poem and puts forward research hypotheses concerning possible reasons for konopnicka’s resignation from the „Fra Angelico. Wniebowzięcie” lyric in the „Italia” volume published in 1901. This work is not mentioned by „Nowy Korbut”, nor by Jan Czubek in his edition of the poet’s works - it can therefore be considered an unknown poem by Maria Konopnicka.